Sex and anti-inflammatory treatment affect outcome of melanoma and non-small cell lung cancer patients with rheumatic immune-related adverse events - Gente, Karolina; Diekmann, Leonore; Daniello, Lea; Will, Julia; Feißt, Manuel; Olsavszky, Victor; Günther, Janine; Lorenz, Hanns-Martin; Souto-Carneiro, Maria Margarida; Hassel, Jessica C.; Christopoulos, Petros; Leipe, Jan (Journal for ImmunoTherapy of Cancer, 2023)
Background Rheumatic immune-related adverse events (R-irAEs) occur in 5-15% of patients receiving immune checkpoint inhibitors (ICI) and, unlike other irAEs, tend to be chronic. Herein, we investigate the factors influencing cancer and R-irAEs outcomes with particular focus on adverse effects of anti-inflammatory treatment. - Methods In this prospective, multicenter, long-term, observational study, R-irAEs were comprehensively analyzed in patients with malignant melanoma (MM, n=50) and non-small cell lung cancer (NSCLC, n=41) receiving ICI therapy who were enrolled in the study between August 1, 2018, and December 11, 2022. - Results After a median follow-up of 33 months, progressive disease or death occurred in 66.0% and 30.0% of MM and 63.4% and 39.0% of patients with NSCLC. Male sex (progression-free survival (PFS): p=0.013, and overall survival (OS): p=0.009), flare of a pre-existing condition (vs de novo R-irAE, PFS: p=0.010) and in trend maximum glucocorticoid (GC) doses >10 mg and particularly ≥1 mg/kg prednisolone equivalent (sex-adjusted PFS: p=0.056, OS: p=0.051) were associated with worse cancer outcomes. Patients receiving disease-modifying antirheumatic drugs (DMARDs) showed significantly longer PFS (n=14, p=0.011) and OS (n=20, p=0.018). Effects of these variables on PFS and/or OS persisted in adjusted Cox regression models. Additionally, GC treatment negatively correlated with the time from diagnosis of malignancy and the latency from ICI start until R-irAE onset (all p<0.05). R-irAE features and outcomes were independent of other baseline patient characteristics in both studied cancer entities. - Conclusion Male sex, flare of pre-existing rheumatologic conditions and extensive GC treatment appeared to be linked with unfavorable cancer outcomes, while DMARD use had a favorable impact. These findings challenge the current dogma of restrictive DMARD use for R-irAE and thus may pave the way to better strategies and randomized controlled trials for the growing number of patients with R-irAE.
Online veröffentlicht: 19. September 2023
Gesehen am 27.11.2023